Frequency and Motivation of ChatGPT Use as Predictors of Academic Performance: The Mediating Role of Perceived Academic Dishonesty - Putri Hestiningrum; Renny Dwijayanti; Saino; Winaika Irawati; Sela Rachmawati (PT Maju Malaqbi Makkarana, 2026)
ChatGPT is one of the AI tools widely used among students. There is debate about whether its use can improve learning outcomes or actually lead to a dependency that declines students' thinking skills. Objective. This study examines the influence of frequency of use and motivation on academic performance, with perceived of academic dishonesty as a mediating variable. The hypothesis was evaluated using Partial Least Squares (PLS) modelling. The results indicated that both the frequency and motivation of ChatGPT use influence academic performance. The structural equation model showed that perceived academic dishonesty mediated the correlation between both frequency of use and motivation to use ChatGPT and academic performance. The study involved 218 undergraduate students from Indonesian universities (39,9% males and 60,1% females; mean age = 20,4, SD = 1,00). The results showed that perceived academic dishonesty partially reduced the positive effect of frequency of use on academic performance, while strengthening the influence of motivation on academic performance. Perceived academic dishonesty played a significant role in determining whether ChatGPT use would have a positive or negative impact on students’ academic performance. Motivation to use ChatGPT proves to be an important factor in determining the direction of this technology’s usage.